Association of MBL2 Exon 1 Polymorphisms With Multibacillary Leprosy - Tiyo, Bruna Tiaki; Vendramini, Evelyn Castillo Lima; de Souza, Victor Hugo; Colli, Cristiane Maria; Alves, Hugo Vicentin; Sell, Ana Maria; Zucoloto, Sylmara Bessani Paixão; Visentainer, Jeane Eliete Laguila (Frontiers in Immunology, 2020)
Mannose-binding lectin (MBL) is a serum protein of innate immunity, with central role in activation of complement system through lectin pathway. This protein is encoded by MBL2 gene, and single nucleotide polymorphisms located at exon 1, such as rs5030737 C>T (D variant), rs1800450 G>A (B variant) and rs1800451 G>A (C variant), may change MBL structure and serum concentration. MBL2 polymorphisms have been associated with several infectious diseases, including leprosy. Host immune response has a major impact on the clinical manifestation of leprosy, since only a few individuals infected with Mycobacterium leprae will develop the disease. Therefore, the aim of this study was to evaluate the influence of MBL2 exon 1 polymorphisms (rs5030737, rs1800450 and rs1800451) on MBL levels and leprosy immunopathogenesis. This case-control study included 350 leprosy patients, 279 classified as multibacillary (MB) and 71 as paucibacillary (PB). Control group consisted of 350 non-consanguineous individuals, which were not diagnosed for leprosy or other infectious and autoimmune diseases. Genotyping was performed by PCR-SSP and MBL serum concentrations were evaluated by ELISA. MBL2 exon 1 polymorphisms were analyzed individually and grouped genotypes, considering “A” as the wild allele and “O” as the presence of at least one polymorphism (D, B or C variants). Differences were not observed in distribution of genotypic and allelic frequencies between leprosy per se patients and controls. However, in haplotypic analysis, the TGG haplotype presented a risk for development of leprosy per se in women when compared to the wild haplotype (CGG) (OR = 2.69). Comparing patients with MB and BP, in a multivariate analysis, B variant was associated with the susceptibility of developing the MB form of leprosy (OR = 2.55). Besides, CAG haplotype showed an increased susceptibility to develop MB leprosy in women compared to men. It was observed that A/O genotype in women was associated with susceptibility to leprosy per se development (OR = 1.66) and progression to MB leprosy (OR = 3.13). In addition, MBL serum concentrations were in accordance with genotyping analysis. In summary, our data suggests that MBL2 exon 1 polymorphisms are associated with an increased risk to leprosy development and progression.